Enhancing docetaxel efficacy and reducing toxicity using biodegradable periodic mesoporous organosilica nanoparticles - Ha Nguyen Van; Linh Ho Thuy Nguyen; Ngoc Xuan Dat Mai; Anh Ha Nhat; Trinh Le Thi Thu; Anh Nguyen Thi Bao; Ha Nguyen Thanh; Minh Tri Le; Tan Le Hoang Doan (Heliyon)
Taxanes, such as docetaxel (DTX), are pivotal in cancer therapy, showcasing remarkable efficacy against various cancers, like breast, lung, and ovarian malignancies. However, DTX's efficacy is hindered by poor target specificity and significant adverse effects. Formulations containing DTX often include polysorbate 80 and ethanol, exacerbating reactions like hypersensitivity and neurological disorders. Nanotechnology offers a promising avenue to address these challenges, aiming to enhance DTX's targeted delivery and solubility. Mesoporous silica nanoparticles (MSN), notably biodegradable periodic organosilane (BPMO), have emerged as promising carriers due to their stability, biocompatibility, and drug-loading capacity. BPMO's intracellular biodegradability reduces the risk of toxic accumulation. Compared to conventional MSN, BPMO particles exhibit superior characteristics, including size, surface area, and DTX loading ability. Moreover, cell line studies suggest BPMO's potential to mitigate DTX-associated adverse effects. These findings highlight BPMO nanoparticles' potential in improving DTX delivery, solubility, and reducing adverse effects, underscoring their significance in cancer therapy.